2006
DOI: 10.1111/j.1945-5100.2006.tb00458.x
|View full text |Cite
|
Sign up to set email alerts
|

Estimating shock pressures based on high-pressure minerals in shock-induced melt veins of L chondrites

Abstract: Abstract-Here we report the transmission electron microscopy (TEM) observations of the mineral assemblages and textures in shock-induced melt veins from seven L chondrites of shock stages ranging from S3 to S6. The mineral assemblages combined with phase equilibrium data are used to constrain the crystallization pressures, which can be used to constrain shock pressure in some cases. Thick melt veins in the Tenham L6 chondrite contain majorite and magnesiowüstite in the center, and ringwoodite, akimotoite, vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 56 publications
1
37
0
Order By: Relevance
“…The latter, classified as "disequilibrium" effects (Stöffler et al 1991), are melt veins (shock veins) and melt pockets observed typically in mafic and ultramafic rocks. It should be emphasized that the high pressure polymorphs, which occur in or near to melt veins and melt pockets (e.g., Chen et al 1996;El Goresy et al 2000, 2003Beck et al 2002;Xie and Sharp 2004;Xie et al 2006aXie et al , 2006b, cannot be used as barometers of the "equilibration" shock pressure as they form in very localized, kinetically favored regions characterized by pressure-temperature spikes.…”
Section: Determination Of "Equilibration" Shock Pressuresmentioning
confidence: 99%
“…The latter, classified as "disequilibrium" effects (Stöffler et al 1991), are melt veins (shock veins) and melt pockets observed typically in mafic and ultramafic rocks. It should be emphasized that the high pressure polymorphs, which occur in or near to melt veins and melt pockets (e.g., Chen et al 1996;El Goresy et al 2000, 2003Beck et al 2002;Xie and Sharp 2004;Xie et al 2006aXie et al , 2006b, cannot be used as barometers of the "equilibration" shock pressure as they form in very localized, kinetically favored regions characterized by pressure-temperature spikes.…”
Section: Determination Of "Equilibration" Shock Pressuresmentioning
confidence: 99%
“…Such phases include lingunite (the highpressure polymorph of NaAlSi 3 O 8 in the hollandite structure) (1,2); stishovite and poststishovite silica phases (3)(4)(5); wadsleyite (6) and ringwoodite (7), the high-pressure polymorphs of (Mg,Fe) 2 SiO 4 in a spinelloid (wadsleyite) and the spinel structure (ringwoodite), respectively; and (Mg,Fe)SiO 3 in the garnet [majorite (8,9)], ilmenite [akimotoite (10)], and arguably the perovskite structure (11,12). Pressures of formation have been estimated from static synthesis experiments of such phases and range up to 26 GPa (12)(13)(14)(15)(16). However, only stishovite has been recovered from shock experiments with very rapid quench and only in small amounts (17)(18)(19).…”
mentioning
confidence: 99%
“…8. Additionally, it has been assumed that the maximum shock temperature in the vein rim was lower than that in the vein center (e.g., Xie et al. 2006a, 2006b).…”
Section: Discussionmentioning
confidence: 99%
“…Thereafter, majorites have been reported from the Suizhou L6 chondrite (Chen et al. 2004), the Tenham L6 chondrite (Xie and Sharp 2007; Xie et al. 2006a, 2006b) and from the Y‐75267 H6 chondrite (Kimura et al.…”
Section: Introductionmentioning
confidence: 99%